The Potential of Banto Royo Tourism Based on Local Wisdom and Islamic Philanthropy towards SDGs Tourism - Rusyaida Rusyaida; Gusril Basril; Anggi Safitri (EKONOMIKA SYARIAH : Journal of Economic Studies, 2022)
Since 2018, the youth and the people of Banto Royo Village, Koto Tangah, have developed several tourism destinations in their area. This village has many potential tourism objects with charm and uniqueness, so many visitors from inside and outside the area enjoy it. Increased visits increase regional income, which returns for social purposes. This research is descriptive qualitative, and data collection is done by observation, interviews, and documentation and is supported by relevant written materials such as books, research, and journals. This study aims to describe the economic advantages of local wisdom-based tourism and its prospects in Banto Royo Village. The results showed that Banto Royo, a tourist destination, has many advantages and uniqueness. In addition to its beautiful scenery, it offers unique and halal culinary delights, a family arena, community friendliness, courtesy, and adequate facilities. The community has a role in participating in carrying out tourism activities by maintaining their local traditions and wisdom. The government and the community are committed to increasing the potential and attractiveness of tourism and improving the community's economy through the Sustainable Development Goals (SDGs).